Omega-3 (ω-3) and social skills interventions for reactive aggression and childhood externalizing behavior problems : a randomized, stratified, double-blind, placebo-controlled, factorial trial - Raine, Adrian (2020)
Background: While studies suggest that nutritional supplementation may reduce aggressive behavior in children, few have examined their effects on specific forms of aggression. This study tests the primary hypothesis that omega-3 (ω-3), both alone and in conjunction with social skills training, will have particular post-treatment efficacy for reducing childhood reactive aggression relative to baseline.